Socioeconomic Background, Preschool Attendance, and Mathematics Achievement in Serbia: Evidence from TIMSS 2023 - Đorđević, Mirjana V; Memišević, Haris; Glumbić, Nenad (Psihološka istraživanja, 2026)
This study examined the associations between preschool attendance, socioeconomic status (SES), gender, and early academic skills, and fourth-grade mathematics achievement in Serbia using data from a nationally representative TIMSS 2023 sample. Method: Mathematics achievement was analyzed using plausible values, and regression models were estimated in the IEA International Database Analyzer while accounting for sampling weights. Predictors were entered in four successive regression models, with socioeconomic background entered first, followed by gender and preschool attendance, and finally early literacy and numeracy skills. Results: Socioeconomic background emerged as the strongest predictor of achievement, while gender and preschool attendance showed smaller but still statistically significant effects. Early literacy and numeracy did not account for additional variance once these factors were considered. Supplementary analyses indicated that longer preschool attendance was particularly beneficial for students from socioeconomically disadvantaged backgrounds, whereas differences were minimal among high-SES students, suggesting a compensatory effect of early childhood education. Conclusion: The results suggest that, while longer preschool attendance can partially compensate for disadvantaged socioeconomic status and contribute to better mathematics achievement, it alone cannot fully offset the strong influence of socioeconomic background, highlighting the need for broader policies that enhance educational quality and reduce educational inequalities.
Keywords: TIMSS; mathematics achievement; preschool education; SES; elementary school